2011
DOI: 10.1097/bpo.0b013e31821adca9
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Failure of Nonoperative Treatment for Type-2 Supracondylar Humerus Fractures

Abstract: Despite adequate reduction and casting of type-2 supracondylar fractures, some fractures will lose reduction and require delayed pinning. The degree of extension of the distal fragment at the time of injury may help to predict the likelihood of failure of nonoperative treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 11 publications
0
20
0
4
Order By: Relevance
“…We found 28 studies examining outcome data of closed reduction and casting for displaced supracondylar fractures. 17–43 This included any method of immobilisation whereby plaster of Paris was applied to the injured arm, set under any degree of flexion. Closed reduction was performed and, where specified, manipulation of the displaced injury was performed under general anaesthetic, local block or sedation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We found 28 studies examining outcome data of closed reduction and casting for displaced supracondylar fractures. 17–43 This included any method of immobilisation whereby plaster of Paris was applied to the injured arm, set under any degree of flexion. Closed reduction was performed and, where specified, manipulation of the displaced injury was performed under general anaesthetic, local block or sedation.…”
Section: Resultsmentioning
confidence: 99%
“…Four studies found casting to be viable first line management. 9,26,28,43 However, all acknowledged a proportion who would require delayed pinning in the event reduction was lost; this was not found to affect long-term outcomes. These papers did not differentiate between Gartland types II and III.…”
Section: Closed Reduction and Castingmentioning
confidence: 99%
“…Controversy remains over a consensus approach to the treatment of Gartland type 2 supracondylar humerus fractures [ 4 ]. Many fractures of this type can be evaluated in the emergency department, splinted/casted, and discharged home to be followed in the clinic or to safely undergo operative treatment on an outpatient basis, avoiding hospitalization [ 8 ]. As the healthcare environment changes and outpatient procedures are further emphasized, there may be an impetus for treatment in this fashion, as it has been shown to be safe and reliable [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…The greater the degree of fracture extension, based on the anterior humeral line, the higher the risk of failure of cast treatment. This was found to be of significance [29]. Other factors in the same study which were found to correlate with failure of treatment include increased width of soft tissue shadow of the upper arm.…”
Section: Gartland Type IImentioning
confidence: 65%